Association between plant-based diets and depression in older adults with heart disease: the mediating role of sleep disturbances - Yaqun Yu; Yueying Cheng; Nan Cheng; Jie Zhang; Qitao Xu; Yawen Wang; Wei Zhou; Chao Yan; Huiqiong Li; Zhiyun Gong (Frontiers in Nutrition)
BackgroundDepression is not uncommon among older adults with heart diseases and is related to poor prognosis at clinical setting. We aim to explore the association between plant-based diets and depression in older adults with heart disease and further investigate the mediating role of sleep disturbances in this relationship.MethodsA cross-sectional sample of 2039 older adults with heart diseases were recruited from the 2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS). Each individual completed assessments on dietary frequency, depression, sleep quality and duration. Plant-based diet index (PDI), healthy plant-based diet index (hPDI) and unhealthy plant-based diet index (uPDI) were calculated. Logistic regression models and restricted cubic spline curves (RCS) were employed to explore the relationship between plant-based diets and depression in older adults with heart disease. Meanwhile, mediation analysis was used to investigate the mediating roles of sleep quality and sleep duration.ResultsThe higher the PDI (OR: 0.56, 95% CI: 0.36–0.88) and the hPDI (OR: 0.39, 95% CI: 0.24–0.62), the lower the risk of depression in older adults with heart disease. Conversely, the higher the uPDI, the higher the risk of depression (OR: 1.76, 95% CI: 1.07–2.92). RCS further confirmed a negative linear dose–response relationship between PDI, hPDI and depression in older adults with heart disease, and a positive trend was found between uPDI and depression. Notably, sleep quality (Indirect effect: −0.031, mediated proportion: 61%) partially mediated the relationship between PDI and depression. In the sex-based subgroup analysis, uPDI was only associated with a higher risk of depression in females.ConclusionThis is the first study to suggest a significant negative relationship between plant-based diets and depression in older adults with heart disease. Sleep quality plays a mediating role in the association between plant-based diets and depression. Optimizing the dietary structure and improve sleep quality may help reduce the risk of depression in older adults with heart disease.